A scoping review of scales and instruments to assess satisfaction in treatment-seeking geriatric population - Newfight Seth; Preethy Kathiresan; Namrata Makkar; Nileswar Das; Siddharth Sarkar (Journal of Geriatric Mental Health, 2025)
Background and Aim: Assessment of treatment satisfaction through scales and instruments enables to quantify the varied aspects of satisfaction, on which interventional pursuits can be based. The aim of this study is to find out the validated instruments that have been used for the treatment satisfaction of the older people. Methods: The scoping review was conducted using PubMed, Google Scholar, and ScienceDirect. Inclusion criteria are research conducted in any healthcare setting and published in an English-language peer-reviewed journal with at least one validated scale assessing the satisfaction of the patient or caregiver. Results: Of the included studies (n = 19), four studies reported at least one validity parameter when used in the geriatric population. Twelve studies measured satisfaction among older persons using scales that were validated for adults. Three studies used scales of satisfaction among caregivers. The majority of the studies are in the English language with a sample size range from 101 to 2385. Cronbach alpha was the most common parameter used for validity. Studies also found that treatment satisfaction was associated with factors such as the severity of diseases, access, availability of doctors, and communication. Similar findings were also observed among caregivers. Conclusion: There is a need to develop and validate scales that measure treatment satisfaction among elder persons, especially in developing country contexts. Wider application of scales and instruments can gear healthcare services toward efforts at improving care satisfaction.